Avaliação do potencial farmacoquímico dos brotos de Myracrodruon urundeuva Allemão (aroeira-do-sertão) como insumo farmacêutico - Galvão, Wellyda Rocha Aguiar (2018)
Myracrodruon urundeuva Allemão (Aroeira-do-Sertão), Anacardiaceae, is one of the most used plants in folk medicine in Northeastern Brazil as an anti-inflammatory, lesion healing and antiulcer agent. This species is threatened with extinction as a result of anthropogenic exploitation. Considering that 40-cm-long shoots produce qualitatively the same pharmacologically active constituents of the inner bark, the goal of this study is to assess the pharmacochemical potential of Myracrodruon urundeuva Allemão (Aroeira-do-Sertão) shoots used as pharmaceutical input. For this purspose, it was performed chemical prospecting of inner bark, stem and leaves of shoots, confirming the presence of chalcones in the inner bark and stem of the shoots. Also, pyrogallic and catechic tannins were found in the inner bark, stems and leaves of the shoots. In addition, the presence of flavonoids could also be confirmed in the of the shoots. The microscopic characterization complemented with histochemical analysis of the shoots revealed the presence of anatomical structures characterized for the species, phenolic compounds in all pharmacogens and abundance of starch in the root. Silica and preparative chromatographic techniques using maize starch, used by Bandeira (2002) to obtain urundeuvin A, were reproducible. The obtaining of fluid extracts of Myracrodruon urundeuva was optimized using 60% hydroalcoholic solution and a 6-hour-long maceration period, followed by percolation. The fluid extracts of inner bark, stem and leaves of shoots were prepared and assessed based on their physicochemical parameters, polyphenol and tannin contents, with values of 117.81, 24.33, 134.59 and 64.26, 19.24, 115.24 mg/mL, respectively. The extracts, after clean up process by solid phase extraction (SPE) had their chemical composition determined by UPLC-QTOF-MS/ MS and the data obtained were submitted to chemometric analysis (PCA and OPLS-DA). A total of 34 compounds were characterized, among them the dimeric chalcones, urundeuvine A, B and C in inner bark, and urundeuvine A in stem of shoots. Moreover, urundeuvine A derivatives and isomers were identified. In the leaves of the shoots, the flavonoids agathisflavone and the polyphenols tri, tetra, penta and hexagalloyl-hexoside were identified. Gastroprotective and anti-inflammatory activities achieved with fluid extracts at the doses of 700 mg/kg and 1000 mg/kg showed that they had positive and similar results between them and were not toxic to HEK-293. The obtained data supports the substitution of the inner bark for the stem and leaves of the shoots in the preparation of phytotherapics.